Emotional attachment and multidimensional self-efficacy: extension of innovation diffusion theory in the context of eBook reader - Waheed, M.; Kaur, K.; Ain, N.; Sanni, S.A. (2015)
Innovation diffusion theory (IDT) has consistently been used to investigate users' technology adoption. However, it neglects the influence of emotions on technology adoption. The study objectives address the integration of emotional attachment and two-dimensional self-efficacy that provides a fresh insight into the investigation of key predictors of eBook reader adoption intention. Quantitative methodology was used and questionnaire data were collected from university students. Probability proportional stratified sampling technique was used to obtain the proportionate sample. The results indicated that the relative advantage, trialability, observability, human-assisted self-efficacy, and individual self-efficacy significantly influence the adoption of eBook readers. However, emotional attachment to paper books negatively influences the relationship between user attitude towards eBook readers and adoption of eBook readers. The results indicate a good measurement model fit and confirmed the validity and reliability of the framework. The integrated framework will be useful in understanding the behavioural and emotional factors associated with the adoption of eBook readers. Moreover, a better understanding of the contributions of assisted and individual self-efficacy for the adoption of any new product or technology will be obtained. The proposed integration will help the managers before introducing a new product in the target market by considering the users' emotional attachment to prior products.